Determination of the Size of Irregular Particles Using Interferometric Out-of-Focus Imaging. (9th January 2014) - Brunel, Marc; Shen, Huanhuan; Coëtmellec, Sébastien; Gréhan, Gérard; Delobel, Tony
Abstract : We present a mathematical formalism to predict speckle-like interferometric out-of-focus patterns created by irregular scattering objects. We describe the objects by an ensemble of Dirac emitters. We show that it is not necessary to describe rigorously the scattering properties of an elliptical irregular object to predict some physical properties of the interferometric out-of-focus pattern. The fit of the central peak of the 2D autocorrelation of the pattern allows the prediction of the size of the scattering element. The method can be applied to particles in a size range from a tenth of micrometers to the millimeter.